Geological features of siliciclastic reservoirs in deep petroleum accumulations - ZHANG Kai-xun; BAI Guo-ping; CAO Bin-feng; JIN Feng-ming (工程科学学报, 2016)
Based on the latest data of deep petroleum accumulations,this study aims at documenting distribution patterns and geological features of global siliciclastic reservoirs. Central South America and North America(excluding the Lower 48 States) host the largest shares of the total proved and probable(2P) oil and gas reserves in deep siliciclastic rocks. North America contains the bulk of 2P oil reserves in deep siliciclastic rocks,whereas Central South America has the lion's share of gas and condensate reserves. Of all deep petroliferous basins with siliciclastic reservoirs,the 6 most prolific basins are the Gulf of Mexico,East Venezuela,Arabian,South Caspian,Tarim and Santa Cruz-Tarija Basins. Deep siliciclastic reservoirs are generally characterized by poor petrophysics. It is fair to say,however,that high-quality sandstone reservoirs could be developed under favorable geological conditions at deep burials.The key of deep petroleum exploration is the better delineation of "Sweet Spots" in deep layers where grain coatings,fluid overpressure and/or well-developed salts might have preserved the considerable portion of original primary porosity.